PERBANDINGAN MUTU MINYAK KELAPA YANG DI PROSES MELALUI PENGASAMAN DAN PEMANASAN SESUAI SNI 2902-2011 (Comparation of Coconut Oil Quality Processed through Acidifying and Heating According to SNI 2902-2011) - Susanto, Tri (Baristand Industri Banda Aceh, 2013)
Heating process commonly used in the production of coconut oil, meanwhilethe acidification process can also be used as an alternative production process by additionof acetic acid at the isoelectric pH. The study was conducted to compare the quality of oilproducts through the process of acidification and heating, by comparing them with thequality requirements of SNI 2902-2011. The results showed that the yield of palm oilthrough acidification process is lower than heating. Based on the physical and chemicaltesting indicated that the quality of coconut oil processed through acidification andheating for the color parameter that is equal to 12/60 - 14/70; moisture and dirt from 0.1 -0.48%, iodine number 6, 8 - 9.8 g Iod/100g; saponification number 243 - 263 mg KOH / gsample; Free Fatty Acid as lauric acid 0.2 -1.26%; unsaponificated material 0.2 - 0.7%;metal contamination Cd 0.006 - 0.05 mg / kg; Pb 0.005 -0.02 mg / kg; Sn 0.007 -0.09 mg /kg; Hg 0.004 - 0.01 mg / kg; As 0.005 - 0.02 mg / kg. Based on the comparison testaverage concentration of the quality parameters coconut oil produced through heating andacidification, the result is above tcritical 1.71 (Î± = 0.05, one-tail test), which means there isno significant difference in the quality of oil processed through heating and acidification. Based on the comparison of the average concentration of each parameter with the qualityrequirements of SNI 2902-2011, the result (tstat) is more than 1.71 (Î± = 0.05), which meansquality of coconut oil for both processes meet the quality requirements of SNI 2902-2011.